Masyarakat Baduy dan pengobatan tradisional berbasis tanaman - Permana, R. Cecep Eka (Wacana, Journal of the Humanities of Indonesia, 2009)
A Baduy community in general is still bound by the traditional rules (pikukuh). One of the pikukuh said lojor teu meunang dipotong, pendek teu meunang disambung, which means "what is long might not be cut off, what is short might not be connected". The implicated meaning pikukuh is that which does not change something or anything, or does not accept what is available without increasing or reducing what is available. This also includes not to accept modern goods or goods made in factories. The inner struggle of Baduy Luar is between on the one hand trying to preserve the customs of theirs ancestors, but on the other hand trying to follow the development in modernity and in their environment. This is reflected in issues related to health. If a Baduy falls ill, the dilemma is to choose between modern medical treatment that increasingly is easily accessible with the consequence to violate the local tradition, or to use the traditional herbs of which the local knowledge is decreasing with the consequence that is more difficult to get this kind of therapy.